Isolation, identification, and time course of human DNA typing from bed bugs, Cimex lectularius. (December 2018) - Schal, Coby; Czado, Natalia; Gamble, Richard; Barrett, Amy; Weathers, Kiera; Lodhi, Khalid Mahmud
Highlights: Adequate quality of human DNA can be obtained from a bed bug up to 4.5 days PBM. Complete human DNA STR profiles can be generated up to 72 h PBM from a bed bug. Single source/multiple host(s) human DNA profile(s) can be typed from a bed bug. Larger sizes STR markers degrade easily compared to medium and smaller size markers. Bed bugs can serve as an evidence in temporal spatial predictions to a location. Abstract: Bed bugs ( Cimex lectularius L.) are ectoparasitic wingless insects that feed on the blood of mammals, typically in residential settings. The objectives of this study were to establish a time-course of human DNA quantitation from bed bugs and to generate human DNA profile(s) of a host and/or multiple hosts from a bed bug that fed on human blood. Female human genomic DNA concentrations ranged from 18.370 to 0.195 ng/bed bug at 0–108 h post blood meal (PBM), male human genomic DNA concentrations ranged from 5.4 to 0.105 ng/bed bug at 0–108 h PBM, and pooled human female and male blood ranged from 5.49 to 0.135 ng/bed bug at 0–96 h PBM. Human autosomal STR complete profiles were obtained until 72 h PBM for female, male, and pooled human blood. These results reveal that identification of multiple human hosts is possible from a single bed bug. However, the ratio of each contributor may be variable depending on the amount of blood ingested from each individual and the time difference of blood consumed from each subject. Average peak heights for three STR markers of low (D3S1358), medium (D13S317), and high molecular weight (D2S1338), were also compared over time. Peak heights were consistently higher for the low molecular weight marker over all time intervals. These data suggest that some markers can be successfully recovered more than three days PBM. Hence, bed bugs can serve as physical evidence in temporal and spatial predictions to match suspects and/or victims to specific locations in criminal investigations.